Detecção de porphyromonas gingivalis e dos genótipos fima II e IV em portadores de periodontite agressiva - Nogueira, Márcia Viana Bessa (2011)
Porphyromonas gingivalis is a pathogen strongly associated with the etiology of chronic and aggressive periodontitis. The purpose of this study was to evaluate by Real-Time polymerase chain reaction (Real Time-PCR) the presence of Porphyromonas gingivalis (Pg) and fimA genotypes type II and type IV in patients with generalized aggressive periodontitis (GAgP). Forty individuals with aggressive periodontitis (AgP) (29.7 ± 8.1 years) were clinical analyzed through plaque index (PI), gingival index (GI), probing depth (PD), clinical attachment level (CAL) and microbiologically, by Real Time-PCR for the presence of Pg and fimA genotypes type II and type IV. Subgingival biofilm samples were collected from the interproximal periodontal sites (> PD and > CAL). The PD and CAL average of this sites were respectively: 9,5 ± 2,2 mm e 10,2 ± 2,8 mm. P. gingivalis was observed in 26 (65%) of individuals. FimA genotypes type II was detected in 16 (61,53%) while fimA genotypes type IV in 7 (26,92%) of those with P. gingivalis. However, no differences were observed between the clinical parameters of patients who presented or not the organism or its genotypes. There was also no association between the presence of genotypes and age or gender of patients. The data suggest an association between P. gingivalis fimA genotypes upon the occurrence of this microorganism in patients with generalized aggressive periodontitis.